Pengaruh Pelatihan Terhadap Kompetensi Karyawan pada PT. Baja Panelindo Utama di Jakarta - Haerofiatna (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the effect of training on employee competence at PT. Steel Panelindo Utama in Jakarta. The method used is explanatory research with a sample of 65 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study of the training variable obtained an average score of 3.805 with good criteria. The employee competency variable obtained an average score of 3.892 with good criteria. Training has a positive and significant effect on employee competence with a regression equation value of Y = 13.040 + 0.680X, and a correlation coefficient value of 0.806 or has a strong relationship with a determination value of 65.0%. Hypothesis testing obtained a significance of 0.000 <0.05.